‘‘The Utilization of Local Multi Microbial With Different Dose and Duration Incubation Time on the Dry Matterand Organic Matter Digestibility of Oil Palm Frond In Vitro’’ - wike sujana (Jurnal Peternakan Integratif, 2016)
ABSTRACT Oil palm frond is one of waste oil palm plantations , where its presence is quite abundant throughout the year in Indonesia , especially North Sumatra . This study aims to assess the ability of microorganisms with dose and different incubation time in improving digestibility of dry matter (DMD) and organic matter digestibility (OMD) of the oil palm frond in vitro. The design used in this study was factorial design using randomized block design. The treatment consists of a dose of P1 (0.2%) and P2 (0.4%) and time incubation 0, 3, 6 and 9 days. Oil palm frond fermented by local microbe (Aspergilusniger + Saccharomyces cerevisiae + bacteria buffalo). The result showed that the dose had significant effect (P 0.05) on the DMD and OMD in vitro. Local multi microbial doses of 0.4% showed higher than 0.2% on the DMD and OMD of oil palm frond. Conversely, incubation time 0 – 9 days did not affect (P> 0.05) the digestibility value. There is no interaction between dose and time incubation on the DMD and OMD. It is concluded that dose localmulti microbial increase digestibility of oil palm frond in vitro. Keywords: Oil palm frond, local multi microbial, dose, incubation time, digestibility, In vitro